Gender based variations of mulligan mobilization with movement on chronic nonspecific low back pain (Bangladesh Journal of Medical Science, 2021)
Objective: To discover the adequacy of mulligan mobilization with movement to lessen the pain to enhance the functional activities, to enhance the ROM of lumbar vertebra and to expand the back muscle function on subjects with chronic nonspecific low back pain.Background of the study: These days, a large portion of the populations are experiencing low back pain comprehensively. It has turned into a main source for inability most likely the population influencing from low back pain has been thought to be understudies and stationary employment laborers. Along these lines investigation goes for diminishing the likelihood of low back pain in those populations by mediating with a method mulligan mobilization with movement (MWM).Materials and methods: This was an experimental examination with sixty subjects between the age group of 18-50 (males and females) with chronic nonspecific low back pain(Natour et al 2015). The length of the examination is thrice a week for four weeks. The examination was hung on Dr.MGR Educational and Research Institute. The subjects in avoidance criteria are specific low back pain (spondylosis, radiculopathy, and spondylolisthesis), intellectual issue, pregnancy. VAS scale, Modified Oswestry Low Back Pain Disability Questionnaire and Finger to Floor test (FFT) were utilized as a result measures.Result: There is vast improvement in the post-test estimations of the VAS Score, MODQ, and FFT of Group A when comparing with Group B. On correlation there is distinction in Group A than Group B. In this way the after effect of the investigation has been found to enhance useful functional activity, ROM and lessens pain.Conclusion: Outcome has been proposed that Mulligan Mobilization with Movement (MWM) with SNAG to the Group A has given huge difference and more noteworthy change when compared with Group B.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.543-549